Ultrathin Cu2O as an efficient inorganic hole transporting material for perovskite solar cells. Issue 11 (2nd March 2016) - Yu, Weili; Li, Feng; Wang, Hong; Alarousu, Erkki; Chen, Yin; Lin, Bin; Wang, Lingfei; Hedhili, Mohamed Nejib; Li, Yangyang; Wu, Kewei; Wang, Xianbin; Mohammed, Omar F.; et al.
Abstract : Ultrathin Cu2 O prepared by a thermal oxidation method was investigated as an efficient hole transporting material for perovskite solar cells. Abstract : We demonstrate that ultrathin P-type Cu2 O thin films fabricated by a facile thermal oxidation method can serve as a promising hole-transporting material in perovskite solar cells. Following a two-step method, inorganic–organic hybrid perovskite solar cells were fabricated and a power conversion efficiency of 11.0% was achieved. We found that the thickness and properties of Cu2 O layers must be precisely tuned in order to achieve the optimal solar cell performance. The good performance of such perovskite solar cells can be attributed to the unique properties of ultrathin Cu2 O, including high hole mobility, good energy level alignment with CH3 NH3 PbI3, and longer lifetime of photo-excited carriers. Combining the merits of low cost, facile synthesis, and high device performance, ultrathin Cu2 O films fabricated via thermal oxidation hold promise for facilitating the developments of industrial-scale perovskite solar cells.